Драматичні елементи у фольклорі – традиція та актуальність - Китевський, М. (Народна творчість та етнографія, 2009)
The researches of the folklore and ethnographic sources underscore, that the dramatic elements exist in the folk art (songs, fairy tales, small folklore genres, children folklore etc.), in customs and in the other forms of the life of the folk. But it's importaint what I mean by the notion "dramatic elements in the folklore". Namely, existence of the action, plot, culmination and denouement, then the place and time of the development of the action, monologue, dialogue in the action, characters, masks, dresses, text, scenography, scenario, director, audience, puppet-show, i. e. the presence of the performance. In this paper special attention is given to some dramatic acting with multitude of the dramatic elements, which are connected with large quantity of the Cristmas holidays. We also drew parallels between traditional forms and new elements of celebration and results of the actualization of some innovations in society. It is worth to refer the carnivals in Vechani and Strumitsa and also celebrations of the Eve in Skopje.